Hypothyroidism in Association with Heart Diseases Among Patients Admitted to Cardiac Care Unit - Habban, Muhannad Ghazi; Ouadh, Mohammed Zuhair Raji (Central Asian Journal of Medical and Natural Science, 2023)
Background: Heart disease is the prominent reason of death globally. Especially associated with modern risk factors such as diabetes, dyslipidemia and hypertension, which are grossly share to development of heart diseases. Thorough management of these risk factors is related with significant lowering of hazard of cardiovascular disease in general Aim of study to assess the relationship between hypothyroidism and heart diseases and which types of heart disease more associated with hypothyroism. Patients and methods: A cross sectional study was conducted at Diwanhyia teaching hospital in Al-Diwanhyia governorate, Iraq. The study was achieved through period from 1st of June 2022 to 1st February 2023. A sample of 80 patients with heart diseases were admitted to cardiac unite in hospital from both sex, above 18 years were included in the study. Result : Eighty patients with mean age 57 years divided in 3 groups according to age. In our sample the heart failure patients were 42.5%, unstable angina were 26.3% and myocardial infarction were 31.2%. Prevalence of hypothyroidism among sample of patients with cardiac problems was 20% and 80% of patients have no such condition, as table 4. Moreover, hypothyroidism presented in patients with heart failure, angina and myocardial infarction was 32.3%, 9.5% and 12% respectively. Conclusion: Hypothyroidism is associated with increased risk of cardiac disease, hypothyroidism are more common in heart failure. Hypothyroidism has a wide spectrum of clinical exhibitions. Not only major variations, but also indirect changes in the circulating pool of thyroid hormone may cause or share to cardiovascular disorder risk.